Desenvolvimento de um método aplicado à determinação de mercúrio em amostras de álcool combustível e solos por geração de vapor frio e espectrometria de absorção atômica - Almeida, Ione Lucenir Silva (2014)
The cold vapor generation coupled to atomic absorption spectrometry was used to develop a simple and efficient methods for the determination of mercury in ethanol fuel and soil samples. In the first chapter, a method for the determination of Hg2+ in ethanol fuel samples diluted with water by atomic absorption spectrometry (AAS) after cold vapor (CV) generation is proposed. The optimized chemical conditions for these procedure were 0,4%, (w/v) NaBH4, 5,0 mol L-1 HCl and 50% (v/v) ethanol concentration. The calibration curve showed a linear response over the studied range (1,0-25,0 μg L-1), with a correlation coefficient of 0,9999 and limits of detection and quantification of 0,06 e 0,19 μg L-1, respectively. The relative standard deviations were lower than 3,2%. The accuracy of the method was estimated by applying the recovery test and recovery values between 94 and 108% were obtained. A sample throughput of 45 h-1 was achieved. Simplicity and sensitivity are among the advantages offered by the proposed method. In the second chapter, using also the cold vapor generation coupled to atomic absorption spectrometry, another method was developed for the determination of HgTotal and Hg2+ in soil samples treated with an alkaline reagent, called Universol®. The selectively reduction of the Hg2+ and CH3Hg+ was performed by use of SnCl2 and NaBH4, respectively. The optimized chemical conditions for the determination of the HgTotal and Hg2+ were, 1,0 % (w/v) NaBH4, 3 mol L-1 HCl, 0,1% (w/v) KMnO4 and 0,75 % (w/v) SnCl2. For the step of sample solubilization, the optimized conditions were 150 mg of the ERM CC580 (500 μL of the 40% v/v Universol®), 500 mg of the soil sample (1000 μL of the 40% v/v Universol®), 0,5% (v/v) antifoam, 1,0 % (w/v) L-cysteine, 30 minutes of the solubilization (60 °C). The accuracy of the procedure was evaluated using a certified reference material (ERM CC580) and by applying the recovery test. The analytical results were in good agreement with the certified reference values of HgTotal at a 95% confidence. The concentration of Hg2+ was consistent with the expected value (HgTotal - CH3Hg+). The value obtained for CH3Hg+ was higher than the certified value, the difference can be explained by the presence of the other organic mercury compounds in the ERM CC580. Recovery values between 98 and 102% were obtained for HgTotal, and 96-100% for Hg2+. The relative standard deviations were lower than 2.7%. The detection limits were 0,07 and 0,08 mg kg-1 for HgTotal and Hg2+, respectively. Five samples were analyzed and HgTotal e Hg2+ concentration was found only in one sample and the values does not exceed the value of prevention (0,5 mg kg- 1), established by the brazilian legislation. The use of Universol® combined with CV AAS technique proved to be simple and efficient for the determination of HgTotal and Hg2+ in soil and sediment samples.